2013
DOI: 10.1186/2228-5326-3-31
|View full text |Cite
|
Sign up to set email alerts
|

Defect-related blue emission from ultra-fine Zn1−xCd x S quantum dots synthesized by simple beaker chemistry

Abstract: It has been possible to incorporate cadmium ions in ZnS quantum dots (QDs). It is studied how the substitution of Cd 2+ ions by zinc ions affects the structural, morphological, and optical properties of ZnS QDs. Zn 1−x Cd x S QDs are prepared by a simple beaker chemistry approach and characterized by X-ray diffraction (XRD), high-resolution transmission electron microscopy, and UV-visible and photoluminescence (PL) spectroscopies. XRD studies confirmed that all the prepared samples are in zinc-blende phase. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Hirai et al reported that the stress (or pressure) on the compounds causes the alteration in relative intensities and lattice strain [26]. It is also reported that increase in lattice parameter leads to shift the XRD peaks toward lower Bragg angle and vice versa [27]. Hence, the increase in lattice parameter was supported by the shifting of XRD peaks toward lower Bragg's angle in treated Mg 3 N 2 sample.…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 49%
“…Hirai et al reported that the stress (or pressure) on the compounds causes the alteration in relative intensities and lattice strain [26]. It is also reported that increase in lattice parameter leads to shift the XRD peaks toward lower Bragg angle and vice versa [27]. Hence, the increase in lattice parameter was supported by the shifting of XRD peaks toward lower Bragg's angle in treated Mg 3 N 2 sample.…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 49%
“…This could be attributed to comparable electronegativity values of Zn (1.6) and Cd (1.7) atom [10]. The patterns of the Au/CdZnS indicated the crystalline peaks at 38° corresponding to (111) peak [11,12].…”
Section: Resultsmentioning
confidence: 73%
“…Further we have also evaluated the lattice parameter values of the Cd x Zn 1−x S and the graphs shown the linear decrease in the lattice constant values for the addition of Zn 2+ ions. [14].…”
Section: Resultsmentioning
confidence: 99%
“…The properties of CdS thin films can be tuned to suit various applications by introducing different amounts of other elements such as zinc. This technique has been used to obtain graded bandgap junctions and lattice matched heterostructures [8][9][10][11][12][13][14][15][16][17]. Theoretically, the bandgap of CdS films can be altered from 2.4 eV to 3.5 eV by introducing zinc in various ratios [10].…”
Section: Introductionmentioning
confidence: 99%